Bank capital buffer, leverage ratio and portfolio risk-return decisions : evidence from Malaysia and Indonesia / Ahmad Kemo Touray - Touray, Ahmad Kemo (2013)
Suboptimal decisions on capital and risk return mixes at banks and corporations in pre-crisis East Asia were blamed more for the 1997/1998 banking and financial crisis. This study investigates, (after a decade of regulatory reforms), how bank managers, in post-crisis East Asia, make short term capital and portfolio risk and return decisions, and how decision on capital affects risk and return and vice-versa; after the imposition of high capital requirements in Malaysia and Indonesia. A simultaneous equation model with partial adjustment framework was applied to analyze annual financial data of sample commercial banks from Indonesia and Malaysia covering a period of 8 years (2000-2007).The system equations were estimated using Full-information Three Stage-least square (3SLS) method. Bank managers’ simultaneous decision on target capital buffer to maintain above the regulatory minimum or their target Leverage ratio were modeled each, separately, with managers decisions on target portfolio risk/target portfolio return for the full sample as well as for another two subsamples. The study estimates and tests the significance of two groups of parameters: coefficients for adjustment speed to target capital, portfolio risk and return (ROE), and coefficients indicating the impact of changes in capital ratios on changes in assets portfolio risk or assets portfolio return (ROE) and vice-versa in scale and direction while controlling for other factors. For capital and risk decision models, full sample models results show that Indonesian banks adjust target capital ratios at speeds faster than the speed at which they adjust target assets portfolio risk (risk-weighted asset ratio), while Malaysian banks do the opposites. The relationship between change in capital and change in assets portfolio risk is, in general, positive and mainly significant in the cases of both countries. This indicates that pure moral hazard was absent in bank managers’ short-term capital and risk decisions during the study periods. Possible explicators for these managerial capital and risk decisions could be bank managers’ private incentives, bankruptcy cost avoidance or regulators effect. Analyses on subsamples revealed important characteristic differences between the restructuring/recovery periods of 2000-2003 and the more financially stable periods of 2004-2007; it further highlighted differences between the two countries’ banks regarding capital structure decisions. Evidences on regulatory pressure on banks via differential impact test for capital buffer level on managers’ capital and portfolio risk decisions are mixed for Indonesia; likely due to regulatory forbearance; and weak in Malaysia perhaps due to high capital levels. For capital and portfolio return decision models, full sample model results show that both Indonesian and Malaysian banks adjust target portfolio ROE at speeds faster than the speed at which they adjust target capital ratios. Based on model significance levels cases, decisions on capital buffer and portfolio ROE management are more important in Malaysian banks capital structure policy, while decision on total leverage and portfolio ROE dominates Indonesian banks capital structure decisions. Subsample analysis has, somewhat, substantiated this conjecture. A finding of positive relationship between a change in bank capital ratios and a change in bank portfolio return measure (ROE) has its precedence in literature. The finding may be explained by signaling or bankruptcy cost hypotheses. Implications and limitations of the study are highlighted at the conclusion.